The impact of vitamin D supplementation on body fat mass in elite male collegiate athletes - Kawashima, I.; Tsukahara, T.; Kawai, R.; Mizuno, T.; Ishizuka, S.; Hiraiwa, H.; Imagama, S. (Nutrition and Metabolism, 2021)
Background: Whether vitamin D supplementation has any effect on body fat percentage, especially among elite athletes, remains unclear. The aim of this study was to evaluate the effect of vitamin D supplementation on serum vitamin D level in elite male collegiate athletes and to analyze its effect on body fat percentage. Methods: We enrolled a total of 42 elite male collegiate athletes in this prospective cohort study. In March 2020, body composition monitoring and blood test were performed. All athletes were provided with vitamin D3 supplement tablets of 25 µg/day. The use of the supplement was dependent on athletes` preference. During the study period, their club activities were stopped for 2 months due to the coronavirus disease 2019 outbreak. A second examination, similar to the first one, was performed after approximately 3 months. Supplement usage by each athlete was also confirmed. The participants were divided into a non-supplement group (without supplementation, n = 15) and a supplement group (with supplementation, n = 27). Results: Regarding baseline data at initial examination, the non-supplement and supplement groups showed significant differences in the mean body fat percentage (9.0% and 12.1%, respectively; P = 0.03) and serum 25(OH)D level (22.7 and 18.5 ng/mL, respectively, P = 0.02). At the time of the second examination, there were no significant differences in the results of both the groups. In terms of mean change value from the first to the second examination, there were significant differences in body fat percentage (1.9 and 0.2%, respectively, P = 0.02) and serum 25(OH)D level (1.7 and 7.2 ng/mL, respectively, P < 0.001) between the two groups. A significant negative correlation was observed between the change ratio of body fat percentage and change value of serum 25(OH)D level (r = - 0.37, P = 0.02). Conclusions: Vitamin D supplementation of 25 µg/day significantly increased the serum 25(OH)D level in elite male collegiate athletes. Vitamin D supplementation may play a role in maintaining athletes` body fat percentage under circumstances where sports activity has decreased.